Analysis of polyphenols in millet and processing effects on antioxidant activity - LI, Liangyu; LING, Yang; HE, Tianfeng; LI, Chaoyang; CAO, Rong-an (Food Science and Technology, 2023)
In this study, millet is used as the raw material to study the composition of millet polyphenols and the effects of different processing interventions on the antioxidant activity of millet polyphenols. The composition of millet polyphenols is determined by liquid analysis, and the effects of different processing interventions on their antioxidant activity are studied through five kinds of processing interventions – boiling, baking, microwave treatment, high-pressure boiling, and extrusion expansion – and the changes are discussed. The millet polyphenols mainly contained three substances: 7-O-β-D-glucopyranosyl-6-C-β-D-glucopyranosylluteolin (C27H30O16), p-coumaric acid (C9H8O3), and isoscoparin-7-O-β-D-glucoside (C28H32O16). The antioxidant activity of millet polyphenols obtained from treatment in five kinds of processing interventions was in the following order: boiling > high-pressure boiling > baking > microwave > extrusion. Boiling was the best processing method to retain antioxidant activity of polyphenols, while extrusion was the least favorable.